On the Same Page: Paper Technology Practices in the Humanities and the Sciences - Musil-Gutsch, Josephine (History of Humanities, 2020)
In Vienna around 1900 the paleographer Theodor von Sickel was searching for a botanist to microchemically analyze samples of medieval paper manuscripts. If the material components (the plant fibers and sizing) of the manuscript paper could be determined, then Sickel would acquire crucial information on the origin, dating, and production methods of the manuscripts. Fortunately for him, he met the Viennese botanist Julius von Wiesner, who was also a pioneer in microscopy, and thus began a remarkable collaboration. I have examined the material objects used in their collaboration—the manuscript samples as well as the objects they were stored in—and have, as a result, been able to identify the collaborators’ practices of knowledge organization and knowledge production. I can thus make the following two interrelated claims: first, that the interdisciplinary collaboration between the sciences and the humanities, represented in this case study by botany and paleography, led to the production of new knowledge, namely, a paleographic dating principle for medieval manuscripts; second, that this new knowledge came about precisely because the practices of knowledge organization and hence of knowledge production, which I have identified as being the practices of paper technology, were shared by the collaborators. The case study examined in this article suggests that, thanks to these shared practices, the divide between the humanities and the sciences at the end of the nineteenth century was not as great as is generally believed.<br